Soil seedbank of the Muda Rice Granary in Northwest Peninsular Malaysia invaded by the Weed Fimbristylis miliacea (L.) Vahl - M, Begum; Juraimi, Abdul Shukor; Man, Azmi; Syed Rastan, Syed Omar; Amarthalingam, Rajan (2008)
The experiment was conducted in the glasshouse at Universiti Putra Malaysia from March 2003 to June 2004 to determine the soil seedbank of Fimbristylis miliacea in the rice fields of the Muda rice granary in Peninsular Malaysia. Six soil cores of 5 cm in diameter and 10 cm depth were sampled from each of 24 fields. All samples from each individual field were bulked and placed in plastic trays of 38 25 10 cm. Soil was moistened as required and emergence of weed seedlings was recorded over a period of one year. After one year, remaining seeds were separated, removed and identified.